1994
DOI: 10.1073/pnas.91.13.5748
|View full text |Cite
|
Sign up to set email alerts
|

A role for molecular genetics in biological conservation.

Abstract: The recognition ofrecent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
153
0
5

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(158 citation statements)
references
References 53 publications
0
153
0
5
Order By: Relevance
“…Fragmented populations of the common toad (Bufo bufo) for example are characterised by significantly lower genetic diversity, survival and developmental homeostasis, compared to larger toad populations (Hitchings and Beebee, 1998). Similarly, remnant populations of the Florida panther (Puma concolor coryi) have, compared with larger populations of the species in western United States, low levels of genetic variation, poor sperm quality and high susceptibility to parasites (Roelke et al, 1993;O'Brien, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Fragmented populations of the common toad (Bufo bufo) for example are characterised by significantly lower genetic diversity, survival and developmental homeostasis, compared to larger toad populations (Hitchings and Beebee, 1998). Similarly, remnant populations of the Florida panther (Puma concolor coryi) have, compared with larger populations of the species in western United States, low levels of genetic variation, poor sperm quality and high susceptibility to parasites (Roelke et al, 1993;O'Brien, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies in 1990s questioned whether wild cheetah's survival was being compromised by their lack of genetic variation, and Caro and Laurenson (1994) pointed out that disease susceptibility and breeding problems were an issue more for captive cheetahs while predation was more important in the wild population. The claims that cheetah lost 90-99% of its variability in one or more bottlenecks (O'Brien, 1994) are questionable as it would require 16 generations of sib-sib mating (N e =2) to lose 99% of genetic variation (Amos and Balmford, 2001). A recent study in Namibia (Castro-Prieto et al, 2011) revealed more variation in Class I MHC, but not Class II MHC and also the amount of DNA sequence variation among the alleles was fairly high thus they could recognize a wide array of foreign proteins.…”
Section: Loss Of Genetic Variabilitymentioning
confidence: 99%
“…This implies that variability loss mainly depends on the size of the lowest population to date and for how many generations it has been held at that level; it is slow compared to the timescales over which conservation biology operates (Amos and Balmford, 2001). Thus, although some studies claimed to show a link between known bottlenecks to low levels of genetic variability like in cheetah (O'Brien, 1994) and in Elephant seals (Hoelzel et al, 1993), closer examination reveals that the expected loss of heterozygosity might be far less than thought (Amos and Balmford, 2001). The level of threat posed by genetic variability considering this aspect is therefore currently not very serious but there is no guarantee that situation will remain the same given the ongoing challenges in threats like habitat degradation, fragmentation, pollution and climate change.…”
Section: Loss Of Genetic Variabilitymentioning
confidence: 99%
“…An emerging role of population genetics, phylogenetics, and phylogeography as indicators of a population's natural history and its future prognosis, provides valuable data for use in the development of conservation management plans for endangered species (O'Brien, 1994).…”
Section: Conservation and The Real Risk Of Extinction Of Tuco-tucosmentioning
confidence: 99%